Deciphering the patterns of genetic admixture and diversity in southern European cattle using genome‐wide SNPs - Upadhyay, Maulik (Evol Appl, 2019)
The divergence between indicine cattle (Bos indicus) and taurine cattle (Bos taurus) is estimated to have occurred approximately 250,000 years ago, but a small number of European cattle breeds still display shared ancestry with indicine cattle. Additionally, following the divergence of African and European taurine, the gene flow between African taurine and southern European cattle has also been proposed. However, the extent to which non‐European cattle ancestry is diffused across southern European cattle has not been investigated thoroughly. Also, in recent times, many local breeds have suffered severe reductions in effective population size. Therefore, in the present study, we investigated the pattern of genetic diversity in various European cattle based on single nucleotide polymorphisms (SNP) identified from whole‐genome sequencing data. Additionally, we also employed unlinked and phased SNP‐based approaches on high‐density SNP array data to characterize non‐European cattle ancestry in several southern European cattle breeds. Using heterozygosity‐based parameters, we concluded that, on average, nucleotide diversity is greater in southern European cattle than western European (British and commercial) cattle. However, an abundance of long runs of homozygosity (ROH) and the pattern of Linkage disequilibrium decay suggested recent bottlenecks in Maltese and Romagnola. High nucleotide diversity outside ROH indicated a highly diverse founder population for southern European and African taurine. We also show that Iberian cattle display shared ancestry with African cattle. Furthermore, we show that Podolica is an ancient cross‐bred between Indicine zebu and European taurine. Additionally, we also inferred similar ancestry profile of non‐European cattle ancestry in different Balkan and Italian cattle breeds which might be an indication of the common origin of indicine ancestry in these breeds. Finally, we discuss several plausible demographic scenarios which might account for the presence of non‐European cattle ancestry in these cattle breeds.